Belle e infedeli. Repliche e variazioni di modelli architettonici del barocco romano nel Settecento europeo - Varagnoli, Claudio (Aesthetica Preprint, 2024)
Replicas, copies, variations more or less faithful to the original architectural ‘text’ have been common, as is well known, throughout Western culture since the classical age. Particular prominence is given to copies of architectural exempla that are above all places of worship, thus endowed with a symbolic charge that transcends the language used. With the 18th century, according to a trend dating back to humanistic philology, the phenomenon disengages itself from devotional presuppositions to take on the sense of a diffusion of courtly models, which may have political and ideological implications that are not secondary. In this context, variations on Roman Baroque themes play an important role, focusing on two particular cases: Bernini’s Sant’Andrea al Quirinale, a Jesuit building, and Francesco Borromini’s San Carlo alle Quattro Fontane. The first model knows a vast and transversal diffusion, from Italian examples to analogous cases in Poland, France, Spain Germany, thanks also to its assumption as a didactic model within the Accademia di San Luca: this is what the drawings of Filippo Juvarra and his school testify to, for example, deriving from the attention paid by Carlo Fontana. Borromini’s work knows an important replica in a 17th century church in Gubbio, but the only case in which the façade is replicated is in the “translation” made in the church of the abbey of Santo Spirito alla Maiella, near Sulmona. There are obviously many examples that can be cited in a discussion in this area. What needs to be noted is that in the 18th century the architectural “copy” did not have a normative value, but tended to extract unpublished qualities from the model. From this point of view, it will be possible to speak of copies only from the 19th century and in parallel with what happens in the world of restoration.